Analisis Resepsi Stuart Hall Pada Tayangan Youtube Narasi TV Episode Prabowo Menjawab - Puput Juniar; Yulianti Fajar Wulandari; Ali Imron Hamid (An Nafi': Multidisciplinary Science, 2025)
This study aims to analyze the audience's reception position toward the “Prabowo Menjawab” episode on Narasi TV’s YouTube channel using Stuart Hall’s decoding theory. The research employs a qualitative approach through observation and interviews. A total of 30 comments were selected from 7,866 comments based on popularity (number of likes, replies, and posting time within the past two months), while interviews were conducted with four informants who had fully watched the video. The findings indicate that the majority of audiences occupy the oppositional decoding position, consciously rejecting the narrative and interpreting the program as a form of political image-building. Some audiences fall into the negotiated position, partially accepting the message while maintaining a critical stance toward its substance. Only a small portion of the audience demonstrates a dominant-hegemonic stance, showing full acceptance of the message. These results suggest that audiences are active in interpreting media content and that media constructions are not always received passively, but can be negotiated or even resisted.